2021
DOI: 10.1111/1471-0528.16915
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with Budd–Chiari syndrome or portal vein thrombosis – a multicentre retrospective cohort study

Abstract: Objective To evaluate current practice and outcomes of pregnancy in women previously diagnosed with Budd–Chiari syndrome and/or portal vein thrombosis, with and without concomitant portal hypertension. Design and setting Multicentre retrospective cohort study between 2008 and 2021. Population Women who conceived in the predefined period after the diagnosis of Budd–Chiari syndrome and/or portal vein thrombosis. Methods and main outcome measures We collected data on diagnosis and clinical features. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…A total of 12 studies were included in the final analysis. [16][17][18][19][20][21][22][23][24][25][26][27] Table 1 summarizes the characteristics of the included studies. Nine studies [16][17][18][19][20]22,23,25,26 were from single centers from various parts of India while three studies were multicentric studies from Europe.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 studies were included in the final analysis. [16][17][18][19][20][21][22][23][24][25][26][27] Table 1 summarizes the characteristics of the included studies. Nine studies [16][17][18][19][20]22,23,25,26 were from single centers from various parts of India while three studies were multicentric studies from Europe.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…Nine studies [16][17][18][19][20]22,23,25,26 were from single centers from various parts of India while three studies were multicentric studies from Europe. 21,24,27 Six studies [19][20][21][22]26,27 reported the outcomes in patients with only EHPVO, one study 24 reported the outcomes in only NCPH and five studies reported outcomes in combined patients. [16][17][18]23,25 Seven studies were of low quality, 16,18,19,[22][23][24]26 while five studies were of medium quality 17,20,21,25,27 (Supplemental Table 1).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations